Pharmacological Screening and Phytochemical Evaluation of Antidiabetic Activity of Asparagasus Racemosus Leaves in Normal and Alloxan-Induced Diabetic Rats - Begum, Shaik. Farhatunnisa (International Journal of Pharmaceutical & Biological Archive, 2021)
Diabetes mellitus is the most common endocrine disorder, affecting more than 300 million people worldwide. These therapies developed along the principles of allopathic are often limited in efficacy, carry the risk of adverse effects, and are often too costly, especially for the developing world. To identify complementary or alternative approaches to existing medications, we studied the antidiabetic potential of leaves of Asparagus racemosus. The acute oral toxicity studies of the extracts revealed no toxic effects up to the levels of 2000 mg/kg body weight. The aqueous and alcoholic extracts of 20 and 30 mg/kg body weight of A. racemosus were screened for the presence of hypoglycemic and antidiabetic activity. In this study, diabetes was induced by a single intraperitoneal dose alloxan monohydrate in 72 h fasted rats. The fasting blood glucose level (FBGL) was carried on the 7th, 14th, and 21st, day and oral glucose tolerance test (OGTT) was measured on the 8th, 15th, and 22nd day. Glibenclamide was taken as the standard and the results are quite comparable with it. The studies were indicated that the leaves of A. racemosus are effective in the regeneration of insulin-secreting β-cells and thus possess antidiabetic activity. The aqueous and alcoholic extracts showed a significant effect in decreasing the FBGL and OGTT of rats and it’s also showed good hypoglycemic activity in normal glycemic rats. The preliminary phytochemical analysis of the extracts of A. racemosus revealed the presence of alkaloids, tannins, saponins, terpenoids, flavonoids, phenolics, and glycosides as the possible biologically active principles.